Pre-dry mixing process of low carbon alkaline-activated cement: Properties and advantages in practical work of construction - Teewara Suwan (2018)
© 2018 Trans Tech Publications, Switzerland. Climate change due to carbon dioxide (CO2) emission is a serious concern in modern society. Cement manufacturing industry world-wide currently contributes approximately 8 % of global CO2 emissions, and this is a serious obstacle for the sustainable development of the cement manufacturing industry. Alkaline-activated cement (AAC) has been proven to be one of alternative cementitious materials which has less disturbance to the environment and can be used as construction materials. However, typical alkaline-activated cement is generally manufactured by mixing raw material with alkaline solutions. It was found that the preparation process of solutions and transportation to construction sites could raise some difficulties in real use. To eliminate the use of the alkaline activator in liquid form and simplify the mixing processes, the development of Just-Adding-Water (JAW) technique was introduced in this research. The results revealed that the alkaline-activated cement manufactured using the pre-dry mix process achieved a 28-day compressive strength very similar to that of typical alkaline-solution mixture in non-oven curing condition. In the pre-dry mixing process, the amount of required water may be slightly higher than that of normal alkaline-solution mixture in order to compensate insufficient water in both mixes and moisture loss during exothermic reaction as well as maintain the workability.